Mutations in pregnancy-associated plasma protein A2 cause short stature due to low IGF-I availability - Dauber, Andrew (2016)
Mutations in multiple genes of the growth hormone/IGF-I axis have been identified in syndromes marked by growth failure. However, no pathogenic human mutations have been reported in the six high-affinity IGF-binding proteins (IGFBPs) or their regulators, such as the met alloproteinase pregnancy-associated plasma protein A2 (PAPP-A2) that is hypothesized to increase IGF-I bioactivity by specific proteolytic cleavage of IGFBP-3 and -5. Multiple members of two unrelated families presented with progressive growth failure, moderate microcephaly, thin long bones, mildly decreased bone density and elevated circulating total IGF-I, IGFBP-3, and -5, acid labile subunit, and IGF-II concentrations. Two different homozygous mutations in PAPPA2, p.D643fs25* and p.Ala1033Val, were associated with this novel syndrome of growth failure. In vitro analysis of IGFBP cleavage demonstrated that both mutations cause a complete absence of PAPP-A2 proteolytic activity. Size-exclusion chromatography showed a significant increase in IGF-I bound in its ternary complex. Free IGF-I concentrations were decreased. These patients provide important insights into the regulation of longitudinal growth in humans, documenting the critical role of PAPP-A2 in releasing IGF-I from its BPs.